Monogenic Disorders of Adrenal Steroidogenesis - Baranowski, Elizabeth S. (Horm Res Paediatr, 2018)
Disorders of adrenal steroidogenesis comprise autosomal recessive conditions affecting steroidogenic enzymes of the adrenal cortex. Those are located within the 3 major branches of the steroidogenic machinery involved in the production of mineralocorticoids, glucocorticoids, and androgens. This mini review describes the principles of adrenal steroidogenesis, including the newly appreciated 11-oxygenated androgen pathway. This is followed by a description of pathophysiology, biochemistry, and clinical implications of steroidogenic disorders, including mutations affecting cholesterol import and steroid synthesis, the latter comprising both mutations affecting steroidogenic enzymes and co-factors required for efficient catalysis. A good understanding of adrenal steroidogenic pathways and their regulation is crucial as the basis for sound management of these disorders, which in the majority present in early childhood.